Syrian Refugees in Jordan and Mental Health : Challenges and Culturally Sensitive Practice - Al-Krenawi, Alean, (Social Sciences E-Books Online, Collection 2025., 2025)
This innovative book provides a thorough and compassionate examination of the lives of Syrian refugees in Jordan, as well as their families. It will equip mental health professionals with the necessary skills to effectively intervene when working with this vulnerable population. What distinguishes this book is its emphasis on the unique challenges that arise from the relationship between Jordanian locals and Syrian refugees, as well as how mental health practitioners can navigate these complexities. It sheds light on the obstacles that such practitioners face in their work and offers valuable insights into how to overcome them.